Cross-sectional associations between physical activity and sedentary time with cardiovascular health in children from the ALSPAC study using compositional data analysis - K. M. Sansum; B. Bond; R. M. Pulsford; A. McManus; A. O. Agbaje; A. M. Skinner; A. R. Barker (Scientific Reports)
Abstract This study adopted a compositional framework to cross-sectionally examine the associations between physical activity (PA) and sedentary time (ST) with vascular structure and function and clustered cardiovascular disease (CVD) risk factors in 4277 children (2,226 girls), aged 10.6±0.2 years. Cardiovascular outcomes included flow mediated dilation, distensibility coefficient, pulse wave velocity and a clustered CVD risk factor score. Time spent in light PA (LPA) and moderate to vigorous PA (MVPA) and ST were determined using accelerometers. Multiple linear regression analyses were adjusted for key covariates with LPA, MVPA and ST entered as compositional exposure variables. Neither LPA, MVPA or ST were significantly associated with the vascular outcomes. The proportion of time spent in MVPA and ST were inversely (unstandardised b=−0.126; P=0.001) and positively (b=0.136; P=0.016) associated with clustered CVD risk in the whole group analysis, respectively. MVPA was negatively associated with clustered CVD risk in boys (b=−0.144; P=0.011) and girls (b=−0.110; P=0.032). Only girls had a positive association between ST and clustered CVD risk (b=0.199; P=0.005). Although no associations were observed for PA and ST with vascular outcomes, these data provide further support for interventions that promote MVPA and minimise ST for reducing risk factors for CVD in children.